2007
DOI: 10.1089/apc.2007.9990
|View full text |Cite
|
Sign up to set email alerts
|

“Getting Me Back on Track”: The Role of Outreach Interventions in Engaging and Retaining People Living with HIV/AIDS in Medical Care

Abstract: This qualitative study investigated the process of engagement in HIV medical care from the perspective of people living with HIV/AIDS (PLWHA). In-depth interviews were conducted with 76 participants in six cities. All participants were considered underserved because of histories of substance use, mental illness, incarceration, homelessness, or cultural barriers to the traditional health care system. A semistructured interview guide elicited narratives related to health care and the role of program intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 26 publications
3
108
0
Order By: Relevance
“…84 Our qualitative research suggested an overlap between missing appointments and dropping out of care that bears some similarity to a cyclical process of attendance and non-attendance found in other qualitative research. 85 However, our survey found some differences between people who had missed appointments in the past year and those who had recently dropped out of care altogether. The survey indicated that younger patients, those who had been diagnosed for longer, those with children and with drug and/or alcohol issues were likely to both miss appointments and disengage from HIV care altogether.…”
Section: Objective 5: Factors Influencing Outpatient Attendancementioning
confidence: 61%
“…84 Our qualitative research suggested an overlap between missing appointments and dropping out of care that bears some similarity to a cyclical process of attendance and non-attendance found in other qualitative research. 85 However, our survey found some differences between people who had missed appointments in the past year and those who had recently dropped out of care altogether. The survey indicated that younger patients, those who had been diagnosed for longer, those with children and with drug and/or alcohol issues were likely to both miss appointments and disengage from HIV care altogether.…”
Section: Objective 5: Factors Influencing Outpatient Attendancementioning
confidence: 61%
“…[56][57][58] Existing federal funding for HIV primary care clinics encourages that enhanced wrap around services can be used for to support this integration. 59 The integration of BPN/NLX treatment with primary care for opioid dependent-patients with HIV has been shown to be feasible in a multi-site demonstration project, 60 and to successfully improve engagement in HIV clinical care in a randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…The body of text analyzed in this approach (310 text segments) was broadened to include experiences of unstable retention in HIV care (i.e., text segments coded as facilitators or barriers of falling out of or re-engaging in routine HIV care) previously identified in the literature as influencing the process of selfsustained retention in care. 18,21 Once selected, segments were unlinked from all codes (including sIMB-based codes) prior to the emergent theme identification analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] In line with these efforts, Amico and colleagues 22,23 recently proposed an application of the Information, Motivation, Behavioral Skills (IMB) model, 24 and more specifically of the IMB model of antiretroviral therapy (ART) adherence, 25 as an explanatory model of how such factors can be systematically organized, identified, and targeted through theoretically informed intervention efforts to support initiation and maintenance in clinical care for chronic medical conditions. This model, the situated Information, Motivation, Behavioral Skills (sIMB) model of Care Initiation and Maintenance for chronic diseases (see Fig.…”
Section: Introductionmentioning
confidence: 99%